226k views
4 votes
. A sequence starts with 180, 120, …. If the sequence is arithmetic, create a recursive and explicit formula for the sequence. If the sequence is geometric, create a recursive and explicit formula for the sequence.

2 Answers

2 votes

Final answer:

If the sequence is arithmetic, the recursive formula is a(n) = a(n-1) - d and the explicit formula is a(n) = a(1) + (n-1)d. The given sequence is not geometric.

Step-by-step explanation:

If the sequence is arithmetic, the recursive formula can be written as:

a(n) = a(n-1) - d

where a(n) is the nth term in the sequence, a(n-1) is the previous term in the sequence, and d is the common difference between the terms.

The explicit formula can be written as:

a(n) = a(1) + (n-1)d

where a(1) is the first term in the sequence and n is the position of the term in the sequence.

Since the given sequence starts with 180, 120, it is not a geometric sequence.

User Maksym Bykovskyy
by
4.1k points
3 votes

Answer:

Arithmetic Sequence


T_n = 240-60n ---- Explicit


T_n = T_(n-1) - 60 --- Recursive

Geometric Sequence


T_n = 270* ((2)/(3))^n ---- Explicit


T_n = T_(n-1) * (2)/(3) ---- Recursive

Step-by-step explanation:

Given


180, 120,....

(a) Assume it is an arithmetic sequence

The explicit formula is calculated using:


T_n = a + (n - 1)d

Where


a = 180


d = 120 - 180


d = -60

So, we have:


T_n = 180 + (n - 1)*-60


T_n = 180 -60n + 60

Rewrite


T_n = 180 + 60-60n


T_n = 240-60n

The recursive function is calculated using:


T_1 = 180


T_2 = 120 = 180 - 60 = T_1 - 60


T_3 = 60 = 120 - 60 = T_2 -60

-


T_n = T_(n-1) - 60

(b) Assume it is a geometric sequence

The explicit formula is calculated using:


T_n = ar^(n-1)

Where


a = 180


r = (120)/(180)


r = (2)/(3)

So, we have:


T_n = 180 * ((2)/(3))^(n-1)

Split


T_n = 180 * ((2)/(3))^n / ((2)/(3))^1


T_n = 180 * ((2)/(3))^n / ((2)/(3))

Rewrite as:


T_n = 180 * ((2)/(3))^n * ((3)/(2))


T_n = 180 * ((3)/(2))* ((2)/(3))^n


T_n = 180 * (3)/(2)* ((2)/(3))^n


T_n = 90 * 3* ((2)/(3))^n


T_n = 270* ((2)/(3))^n

The recursive function is calculated using:


T_1 = 180


T_2 = 120 = 180 * (2)/(3) = T_1 * (2)/(3)


T_3 = 80 = 120 * (2)/(3) = T_2 * (2)/(3)

-


T_n = T_(n-1) * (2)/(3)

User Adrien Castagliola
by
5.0k points